2022
DOI: 10.1002/open.202200208
|View full text |Cite
|
Sign up to set email alerts
|

Introducing N‐Heteroaromatic Bases into Copper(II) Thiosemicarbazon Complexes: A Way to Change their Biological Activity

Abstract: Three new copper(II) complexes, [Cu(1,10-Phen)(L)] (1), [Cu(2,2'-Bpy)(L)] ( 2) and [Cu(3,,10-Phen = 1,10-phenanthroline, 2,2'-Bpy = 2,2'-bipyridine, 3,4-Lut = 3,4-lutidine, have been synthesized and characterized by elemental analysis, FTIR spectroscopy and single crystal X-ray crystallography (1, 2). All compounds are mononuclear. The introduction of a monodentate N-heteroaromatic base (3,4-dimethylpyridine) has led to a significant increase of antimicrobial activity against Gram-negative Escherichia coli and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In the literature, cases of similar systems with thiosemicarbazones are described, in which introducing a bidentate N -heteroaromatic base into the inner sphere of copper(II) complexes also did not lead to an increase in antioxidant activity. 27 The antioxidant activity of coordination compounds is influenced by the nature of the central atom, and the activity decreases in the following order: Fe 3+ > Cu 2+ > Ni 2+ . In the literature, there are numerous cases where copper complexes are identified as the most active antioxidants toward ABTS +• cation radicals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, cases of similar systems with thiosemicarbazones are described, in which introducing a bidentate N -heteroaromatic base into the inner sphere of copper(II) complexes also did not lead to an increase in antioxidant activity. 27 The antioxidant activity of coordination compounds is influenced by the nature of the central atom, and the activity decreases in the following order: Fe 3+ > Cu 2+ > Ni 2+ . In the literature, there are numerous cases where copper complexes are identified as the most active antioxidants toward ABTS +• cation radicals.…”
Section: Resultsmentioning
confidence: 99%
“…23 Thiosemicarbazones and their coordination compounds manifest antioxidant activity, often exhibiting values that exceed the activity of medicines used as antioxidants. [24][25][26][27] Studies of the antioxidant activity of pyruvic acid have shown that it has potential for controlling inflammation and preventing diseases caused by oxidative stress. 28 The aim of the present investigation is the synthesis of 1) and its 3d metal coordination compounds, which include bidentate N-heteroaromatic bases such as 1,10-phenanthroline (1,10-Phen) and 2,2′-bipyridine (2,2′-Bpy), along with studies of the antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free radicals play a significant role in various detrimental biological processes, including protein denaturation and lipid peroxidation, contributing to the development of numerous human diseases [39,40]. Hence, investigating the antioxidant potential of the synthesized compounds becomes crucial to determine whether they can mitigate the levels of free radicals and provide protection against oxidative stress in the human body.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…39. Selected FT-IR data, ν (cm −1 ): ν(NH amide II) 3154, ν(CH Aryl) 3060, ν(C=Npy) 1509, ν(C-S) 675, the full spectrum is shown in FigureS4.…”
mentioning
confidence: 99%